Koroner arter by pass greft cerrahisi uygulanan hastaların konfor düzeyi - Üstündağ, Hülya (My University, 2009)
Araştırma, koroner arter bypass greft (KABG) cerrahisi uygulanan hastaların konfor düzeyini belirlemek amacıyla 240 hasta ile yapıldı. Veriler Bireysel Özellikler Formu, Erken Postoperatif Konfor Ölçeği (EPKÖ), Genel Konfor Ölçeği (GKÖ), Durumluk-Sürekli Anksiyete Ölçeği (STAI) kullanılarak yüz yüze görüşme yöntemi ile toplandı. Çalışma kapsamına alınan hastaların yaş ortalamalarının 58.58, %71.2’sinin erkek, %79.1’inin ilköğretim mezunu olduğu belirlendi. Erken postoperatif konfor düzeyi altı üzerinden 5.06±0.50, genel konfor düzeyi dört üzerinden 3.33±0.24 bulundu. Anksiyete düzeyinin alt sınırı 20 iken, durumluk anksiyete düzeyi 31.05±6.80, sürekli anksiyete düzeyi ise 41.78±8.58 olarak bulundu. Hastaların erken postoperatif ve genel konfor (rs=0.56 p<0.001) düzeyi artışı paraleldir. Buna karşın, erken postoperatif ve genel konfor düzeyi artarken durumluk (sırasıyla rs=-0.47, rs=-0.49 p<0.001) sürekli (sırasıyla rs=-0.25, rs=-0.38 p<0.001) anksiyete düzeylerinin azaldığı görüldü. Elde edilen verilere göre KABG uygulamasının konforu düşürmediği tam tersi rahatsızlık veren göğüs ağrısı, dispne, fiziksel fonksiyonlarda azalma gibi semptomları ortadan kaldırarak hastaları rahatlattığı, konfor ile anksiyetenin zıt bir ilişki içinde olduğu kadınların, eğitim düzeyi düşük olanların ve aylık geliri sağlık giderlerini karşılamayanların anksiyetelerinin yüksek, konforlarının düşük olduğu söylenebilir. Konfor, hemşirelik, koroner arter bypass greft cerrahisi, postoperatif bakım.

The Comfort Level of Patients Who Underwent Coronary Artery Bypass Graft Surgery This study was conducted on 240 patients, who undergone coronary artery bypass graft operation (CAGB), to determine their comfort level. The data has been collected by one-on-one interview method by the use of Individual Data Form, Perianesthesia Comfort Questionnaire (PCQ), General Comfort Questionnaire (GCQ), and State-Trait Anxiety Scales. The average age of the patients within the scope of this study has been determined to be 58.58, of which 71.2% is male, and 79.1% is primary school graduates. The early postoperative comfort level has been found as 5.06 ± 0.50 on the scale of 6.0, and the general comfort level has been found as 3.33 ± 0.24 on the scale of 4.0. While the lower bound of anxiety scale was 20, the state anxiety scale has been determined as 31.05 ± 6.80, and trait anxiety scale has been determined as 41.78 ± 8.58. The patients’ early postoperative and general comfort levels (rs = 0.56 with p < 0.001) climb in parallel. Nevertheless, it has been observed that while the early postoperative and general comfort levels increase, state (rs = -0.47 and rs = -0.49 with p< 0.001, respectively) and trait (rs = -0.25 and rs = -0,38 with p<0001, respectively) anxiety levels decrease. According to the data obtained, it can easily be concluded that CABG does not reduce comfort; on the contrary, it relieves the patients by suppressing the symptoms like chest pain, dyspnea and the reduction in physical functions, and that the comfort and anxiety are in adverse relation. Furthermore, the patients, such as women, and/ or those who have low level of education, and/ or those who can not afford their medical expenses, have high level of anxiety and low level of comfort. Key World: Comfort, nursing, coronary artery bypass graft, postoperative care.
Keywords: Cerrahi Hastalıklar; Hemşirelik; Kalp Hastalıkları; Konfor